Försöksplanering och DMAIC i praktiken : En fallstudie vid BDX Industri AB - Malmelöv, Niklas (2016)
Design of experiments is a method to investigate how different factors affect a process. The method is able to be used within the manufacturing industry to achieve how to adjust different factors in a process in order to improve the results i.e. reduce the number of quality deviations. To reduce the quality deviations could also affect cost savings. Design of experiments could be used together with the problem solving method DMAIC (Define, Measure, Analyze, Improve, Control).The purpose of this thesis is to illustrate how Design of Experiments could be used together with DMAIC to achieve cost savings in manufacturing companies. In order to reach the purpose a case study has been performed at the briquette factory of BDX Industri AB in Svartöstan in Luleå. In the briquette factory, briquettes are made of residue from the steel production in SSAB.The briquettes are then delivered to the steel production in SSAB. The case study is performed as a DMAIC-project. The case study started to investigate the savings potential in the production. Then the parameters, which were expected to affect the saving potentials, were identified. In the next step all identified parameters were included in a factor experiment. Next, a factor experiment was performed with all parameters included which affected the hardness of the briquettes according to the first factor experiment. The results then were verified with further factor experiments to confirm the reproducibility of the results.The results of the case study show that increasing the moisture content to the recommended level will make it possible to decrease the cement content and thereby decrease the cost which means a cost saving. The cost savings has also been practically verified.BDX industry AB is recommended to investigate the possibilities to increase the moisture level to the recommended level which makes it possible to decrease cement content and thereby the costs.Further it is recommended to investigate how much the curing chamber time could be decreased in order to ...